Estructura productiva y crecimiento económico en México: Una perspectiva multisectorial - Fidel Aroche Reyes (Investigación Económica, 2019)
– The Mexican economy has shown four decades of slow growth; still it would be reasonable to expect changes in its productive structure along such a long period of time considered, as a result either of the embodied technical change or as a result of the economic policies, that have sought the integration with the US economy, among other causes. According to the so called "Kaldor-Verdoorn law", growth is explained by the behaviour of both output and the manufacturing productivity; hence, in Mexico this sector must have lost its ability to induce growth in the economy as a whole. This paper examines such hypothesis from a structural perspective, considering such law, estimating also the output multipliers á la mode de Miyazawa.
Keywords: O41; O47; C67; D57; O54; 330; Economic growth; Input-Output model; Kaldor-Verdoorn law; Mexican economy